Penerapan Media Sosial Sebagai Sarana Kolaboratif Dalam Pembelajaran Bahasa Arab - Kholil, Muhammad; Salim, Muhammad Bayu; Munir, Dede Rizal (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Collaborative learning models are important in the educational context, both among university students and school students. This approach encourages students to be active, interactive, and collaborate in completing academic tasks, in contrast to conventional models which tend to be one-way. In the context of learning Arabic using a blended learning model, social media such as Instagram, Whatsapp, and TikTok are recommended considering the advantages and disadvantages of each. Collaborative learning provides benefits for students, including recognition of differences, individual recognition, a sense of responsibility, development of cooperation to achieve common goals, helping each other in understanding problems and finding solutions, providing positive responses, and developing common views and a sense of mutual dependence.